Improving the Quality of the Learning Process through Fun Thinkers Learning Media in Elementary Schools - Ery, Ni Kadek Dwi; Rati, Ni Wayan; Agustiana, I Gusti Ayu Tri (Universitas Pendidikan Ganesha, 2024)
Education today continues to develop to improve its quality standards through various aspects of implementing satisfactory learning. The main components involved include human elements, materials, facilities, and learning processes. The lack of learning media used by educators, especially media that can cover material from the core of learning, causes low student interest in learning. Interesting and innovative learning media can increase student motivation and interest in learning. The purpose of this study was to produce Fun Thinkers learning media for grade II elementary school on theme 1 living in harmony. The model used in the study is the ADDIE model. The research method used is the questionnaire method and for data collection instruments using the rating scale instrument. Meanwhile, for data analysis techniques in conducting validity tests using the average score formula and reliability tests using the Percentage of Agreement formula. The results of the research that has been carried out on the validity test of learning media showed that the learning media has very good qualifications based on expert assessments, teachers and students as users. Based on the results of the analysis, the Fun Thinkers learning media for grade II elementary school on theme 1 living in harmony is said to be valid and suitable for use in the learning process.